Between developmentalism and populism : walking a tightrope in Southeast Asia - Trajano, Julius Cesar I (2013)
Southeast Asian economies remain resilient to weak global growth primarily due to buoyant domestic consumption backed by strong government spending. Given the scarce resources of governments, they have to strike a balance between populist measures and fiscal discipline.